EMPLOYING LINE APPLICATION FOR ENGAGING 'GADGET-FREAK' HIGH INTERMEDIATE STI'DENTS AT LBPP LIA PEKANBARU - Dewi Sari Wahyuni (Universitas Negeri Padang, 2015)
The gap between digital immigrant teachers and di-qital native students is inevitable. Prohibition o1 using gadgets in the classroom resulted in decreasing students' enthusiasm and participation in classroom activities. Therefore, this research was carried out. It',rvas based on the difficulty that the researcher as a teacher faced in engaging student to reach the targeted outcomes. LINE application was choosen for this investigation since it is applic,gble for smartphones and tablet computers as well as personal computers. The said application is also considered as one of the most frequent social network messengers used by these teenagers students in communicating with each other and it enabled the teacher to fit into students' place. Observation of l7 students has revealed that incorporating LINE was increasing not only the engagement of the students toward learning, but also their language skills. This is because the real-life collaboration existed among the students and the teacher. It was amazing to see how these young digital natives thrived on technology mediated by their gadgets. Meanwhile, the digital immigrant teacher, hardly struggled with adapting it. Although the lack of technology skills of the teacher sometimes slowed down the process of engagement, the teacher still managed to be in line with the students. On the contrary, there was so much temptation in misusing the gadgets for distracting purposes, which also turned out to be another problem to come to grips with. Despite those predicaments, employing LINE indeed worked well for engaging 'gadget-freak' High Intermediate students at LBPP LIA Pekanbaru.